Bioconversion of glycerol waste to ethanol by Escherichia coli and optimisation of process parameters - Reddy, Chilakamarry Chaitanya; Mimi Sakinah, A. M.; Zularisam, A. W.; Khilji, Irshad Ahmad; Sirohi, Ranjna; Reddy, Venugopal Jayarama (CSIR-NIScPR, India, 2022)
Biofuel is one of the best ways to reduce our dependence on fossil fuels. Ever since commercial biodiesel production began, waste glycerol, the biodiesel byproduct, has gained researchers’ interest, especially its recycling. Here, we explored using glycerol residue (carbon source) as a substrate in the fermentation process for ethanol production by Escherichia coli K12 in anaerobic conditions. The factors affecting the ethanol production was optimised by response surface methodology (RSM). Significant variables that impact the ethanol concentration were pH, temperature and the substrate, with a statistically significant effect (P <0.05) on ethanol formation. The significant factor was analyzed by the Box-Behnken design. The optimum conditions for bioethanol formation using glycerol as substrate was obtained at pH 7 and temperature 37°C. The ethanol productivity was 0.77 g/L/h. The ethanol concentration of 9.2 g/L achieved from glycerol residue was close to the theoretical value with the fermentation achieved at optimised terms.